Karakteristik Penderita Laryngopharyngeal Reflux di Bagian THT-KL RSUP Dr. M. Djamil Padang Tahun 2019 - Fitrahul Afifah; Fachzi Fitri; Arni Amir (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: LPR is often not diagnosed by ENT doctors because of its atypical symptoms, so patients often go to a doctor for help with the same symptoms, but although the doctor gives treatment, the symptops keep recurring.Objective: This study aims to determine the characteristics of patients with laryngopharyngeal reflux in the ENT department of RSUP Dr. M. Djamil Padang in 2019.Methods: This study was a retrospective descriptive study by taking secondary data in medical records of LPR patients at RSUP Dr. M. Djamil Padang period 1 January – 31 December 2019 and used a total sampling technique. The data were analyzed univariately to find the frequency distribution.Results: The total number of LPR patients was 106 patients with 50 people fulfilling the inclusion criteria; the majority of LPR suffers are women (70%); the largest age group is 51-60 years (34%); the most BMI group were 18.5–25.0 (46%); the most symptom is globus pharyngeus (88%); the most common finding of flexible laryngoscopy is erythema (60%); the most prescribed was lansoprazole (82%), whereas the most combination therapy was lansoprazole, N.Acetylcysteine, and sucralfate (14%).Conclusion: The majority of LPR suffers have a normal body mass index, the most combination theraphy are lansoprazole, N. Acetylcysteine, and sucralfate.